The association of donor and recipient age with graft survival in paediatric renal transplant recipients in a European Society for Paediatric Nephrology/European Renal Association-European dialysis and transplantation association registry study - Chesnaye, Nicholas; Schaefer, Franz; Tönshoff, Burkhard (Nephrology, dialysis, transplantation, 2017)
AbstractBackground. The impact of donor age in paediatric kidney transplantation is unclear. We therefore examined the association of donor-recipient age combi